(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2011)
The study application of intertextuality learning model using the CD learning has been conducted in 3 high schools, SMA A, SMA B, and SMA C, during on May 2010. Selection of these three schools are expected to represent the school with low quality to high quality. During the process of learning trials take place, students can actively follow by providing a good response. From the displays are given, students can grasp the concepts of salt hydrolysis on the material well, although sometimes these views should be given back and forth for three levels of representation can link. In general, students responded well to the implementation of this intertextual learning strategy because it was interested in the learning process is done and easy to understand the concepts provided in a systematic and always connects with concepts already learned. The response of teachers towards the implementation of this intertextual learning model provides a positive outlook, in this case because the learning process undertaken to facilitate teachers to deliver material salt hydrolysis systematically arranged through third-level engagement representations and packaged in a multimedia form so that the concepts presented to received by students in one piece and easy. Application of learning models on material intertextual salt hydrolysis was able to improve the mastery of the concepts in the material. Increasing students’ mastery of the concept of material obtained by hydrolysis salt N-gain value calculation, the overall values obtained N-gain of 0.67 which means the implementation of learning strategy on material intertextual hydrolysis of this salt can enhance the mastery of concepts with high criteria. This data also supported students’ mental models for dissolution process of various salts. This model was also to increase student motivation in learning. Increased student motivation most high school students owned by C, which in most low pretest value compared other high school.